Perceived effectiveness of HPV test as a primary screening modality among US providers - Cooper, Crystale Purvis (Prev Med, 2015)
BACKGROUND: The human papillomavirus (HPV) test, administered alone without the Papanicolaou (Pap) test, was recently recognized as a cervical cancer screening option in the United States by the Society of Gynecologic Oncology and the American Society for Colposcopy and Cervical Pathology, and the Food and Drug Administration has approved an HPV test for primary screening. METHODS: Surveys of US internists, family practitioners, nurse practitioners, and obstetrician–gynecologists were conducted in 2009 and 2012 to investigate providers’ perceptions of the effectiveness of the HPV test administered alone as a population-based screening modality (2009: N = 1040, 141–494 per provider group; 2012: N = 1039, 155–435 per provider group).). RESULTS: The majority in each provider group agreed that the HPV test administered alone is an effective screening modality in 2009 (75.3%–86.1%) and 2012 (79.5%–91.8%), and agreement rose significantly during this time period among family practitioners (χ(2) = 15.26, df = 1, p < 0.001) and nurse practitioners (χ(2) = 4.53, df = 1, p = 0.033). CONCLUSIONS: Agreement that the HPV test administered alone is an effective cervical cancer screening modality was widespread among providers in both 2009 and 2012, however implementation of guidelines for screening with the HPV test may be influenced by many other factors including reimbursement and patient preferences.